SPEAKING PROBLEMS FACED BY THE ENGLISH DEPARTMENT STUDENTS OF SYIAH KUALA UNIVERSITY - Heriansyah, Hendra (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2012)
This paper discusses the difficulties and causes perceived by English Department students of Syiah Kuala University in learning speaking and the efforts made by them to overcome their difficulties. From both observation and interview, this study reveals that all students encountered various difficulties in English speaking ability. The prevalent problem faced by the students was ‘lack of vocabulary’, while ‘being afraid of making mistakes’ was the prime cause of problem which hindered them to speak. The students had striven to cope with their problems in learning speaking, but their attempts had not been yet ample and successful.